Effects of dietary Bacillus cereus G19, B. cereus BC-01, and Paracoccus marcusii DB11 supplementation on the growth, immune response, and expression of immune-related genes in coelomocytes and intestine of the sea cucumber (Apostichopus japonicus Selenka). Issue 2 (August 2015) - Yang, Gang; Tian, Xiangli; Dong, Shuanglin; Peng, Mo; Wang, Dongdong
Abstract Probiotics have positive effects on the nutrient digestibility and absorption, immune responses, and growth of aquatic animals, including the sea cucumber (Apostichopus japonicus Selenka). A 60-day feeding trial was conducted to evaluate the effects of Bacillus cereus G19, B. cereus BC-01 and Paracoccus marcusii DB11 supplementation on the growth, immune response, and expression level of four immune-related genes (Aj-p105, Aj-p50, Aj-rel, and Aj-lys) in coelomocytes and the intestine of juvenile sea cucumbers. One group was fed the basal diet (control group), while three other groups were fed the basal diet supplemented with B. cereus G19 (G19 group), B. cereus BC-01 (BC group), or P. marcusii DB11 (PM group). The growth rate of sea cucumbers fed diets with probiotics supplementation was significantly higher than that of the control group (P < 0.05). Sea cucumbers in the G19 and PM groups had a significantly greater phagocytic activity of coelomocytes compared to the control group (P < 0.05), while those in the G19 and BC groups had a greater respiratory burst activity (P < 0.05). The alkaline phosphatase (AKP) activity of coelomocytes in sea cucumbers fed diets with probiotics supplementation was significantly higher than the control group (P < 0.05). Comparatively, superoxide dismutase (SOD) activity of coelomocytes for sea cucumber in the PM group was significantly greater (P < 0.05). As for the immune-related genes, B. cereus G19 supplementation significantly increased the expression level of the Aj-rel gene in coelomocytes (P < 0.05), while B. cereus BC-01 supplementation significantly increased that of the Aj-p50 gene as compared to the control group (P < 0.05). In the intestine, the relative expression level of Aj-p105, Aj-p50, and Aj-lys genes in the PM group was significantly higher than that in the control group (P < 0.05). These results suggested that B. cereus G19 and B. cereus BC-01 supplementation could improve the growth performance and the immune response in coelomocytes, while P. marcusii DB11 supplementation could have a positive effect on the growth performance and immune response in coelomocytes and the intestine of sea cucumbers.